2019
DOI: 10.1016/j.saa.2018.07.078
|View full text |Cite
|
Sign up to set email alerts
|

Spectral classification for diagnosis involving numerous pathologies in a complex clinical setting: A neuro-oncology example

Abstract: Much effort is currently being placed into developing new blood tests for cancer diagnosis in the hope of moving cancer diagnosis earlier and by less invasive means than current techniques, e.g., biopsy. Current methods are expected to diagnose and begin treatment of cancer within 62 days of patient presentation, though due to high volume and pressures within the NHS in the UK any technique that can reduce time to diagnosis would allow reduction in the time to treat for patients. The use of vibrational spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Hands et al [30] reported serum diagnostic of brain tumours using ATR-FTIR spectroscopy with support vector machines (SVMs) with the sensitivity of 89.4% and specificity of 78.0% to distinguish cancerous from non-cancerous samples and the sensitivity of 82.1% and specificity of 75.0% to distinguish glioma from meningioma tissue. Bury et al [31] reported the use of ATR-FTIR spectroscopy to analyse plasma samples in order to distinguish non-cancer from different cancerous brain samples. Normal and meningioma samples were differentiated with 87% accuracy using PCA-LDA and 95% accuracy using SVM, and meningioma samples were diagnosed among several groups of samples (normal, high-grade glioma, low-grade glioma and brain metastasis) with an accuracy of 63% using PCA-LDA and an accuracy of 100% using SVM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hands et al [30] reported serum diagnostic of brain tumours using ATR-FTIR spectroscopy with support vector machines (SVMs) with the sensitivity of 89.4% and specificity of 78.0% to distinguish cancerous from non-cancerous samples and the sensitivity of 82.1% and specificity of 75.0% to distinguish glioma from meningioma tissue. Bury et al [31] reported the use of ATR-FTIR spectroscopy to analyse plasma samples in order to distinguish non-cancer from different cancerous brain samples. Normal and meningioma samples were differentiated with 87% accuracy using PCA-LDA and 95% accuracy using SVM, and meningioma samples were diagnosed among several groups of samples (normal, high-grade glioma, low-grade glioma and brain metastasis) with an accuracy of 63% using PCA-LDA and an accuracy of 100% using SVM.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins play an important role in the molecular pathways for meningiomas, where, for example, integrin exhibits different expression profiles within different grades of meningioma [32]. In addition, Amide I, Amide II and carbohydrate absorptions have been associated with differences between normal and meningioma tissues [31], and δ(CH), δ(CH 3 ), v(C-O) and v as (PO 2 − ) have been found to be related to spectral markers associated with brain tumours in general [30]. These findings indicate that IR spectroscopy allied with chemometrics could be used to aid clinical differentiation of grade I and grade II meningioma tumours in a non-destructive, fast and sensitive way.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial typing and identification by FT-IR can be applied to the fields of general microbiology 21,52,53 , rapid identification of life-threatening pathogens 29,54 , epidemiological investigations and pathogen screening 14,55,56 , characterization and screening of microorganisms from the environment 9,57,58 , and maintenance of strain collections 59 . The audiences include the investigator and operators in microbiology and related fields.…”
Section: Application Of the Methodsmentioning
confidence: 99%
“…Bacterial typing and identification by FT-IR can be applied to the fields of general microbiology 21,52,53 , rapid identification of life-threatening pathogens 29,54 , epidemiological investigations and pathogen screening 14,55,56 , characterization and screening of microorganisms from the environment 9,57,58 , and maintenance of strain collections 59 . The audiences include the investigator and operators in microbiology and related fields.…”
Section: Application Of the Methodsmentioning
confidence: 99%